LIPID-POLYMER HYBRID NANOPARTICLES AND SILICA-BASED HYBRID NANOPARTICLES FOR CANCER TREATMENT - KAILAS, ANJANA A.; RAMA, ANNAMALAI; LADANI, BHAUTIK; GOVINDAN, INDUJA; ABUTWAIBE, K. A.; NAHA, ANUP (International Journal of Applied Pharmaceutics, 2025)
The development of complex nanoparticles with enhanced tumor therapy selectivity and effectiveness is now achievable thanks to nanotechnology. Despite the vast number of nanostructures, such as liposomes, solid-lipid nanoparticles, Lipid-Polymer Hybrid Nanoparticles (LPHNPs), and Silica-based Hybrid Nanoparticles (SHNPs), have been developed as carriers for drug delivery for different pathologies with remarkably promising results. In the present study, we have discussed simple and efficient preparation methods for lipid-polymer and silica-based nanoparticles. These methods reduce the potential for toxicity as the drug molecules can be delivered to the pharmacological sites of action at an optimal controlled rate. With adequate preparation methods, lipid hybrid and silica-based nanoparticles can be developed to reduce adverse effects. Significant improvement has been made in preparing and functionalizing the hybrid nanoparticle for advancing cancer treatment. Studies prove that LPHNPs have exhibited drug-loading efficiency of around 60-70%, which is more than liposomal systems. The ability of these nanoparticles to circulate through the Reticulo-Endothelial System (RES) also results in a significant increase in circulation time, with a half-life of up to 12 h. These hybrid nanoparticles with high drug loading efficiency and specific targeting efficiency can help precisely target the tumor cells.